Analisis Curahan Waktu Kerja Perajin Tenun di Desa Pringgasela Selatan Kecamatan Pringgasela Kabupaten Lombok Timur - Haryono, Salsabila Naqiya; Fadliyanti, Luluk; Purwadinata, Subhan (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the work time allocation of traditional weavers in Pringgasela Selatan Village, East Lombok Regency, as well as the factors that influence it, namely age, education, work experience, and number of family dependents. The village is known as a center of traditional Sasak weaving, passed down through generations and serving as a key source of income, particularly for women. The study employed a descriptive quantitative approach using survey questionnaires. A total of 77 respondents were selected purposively, specifically those with at least five years of weaving experience. Data were analyzed using multiple linear regression. The results showed that the average weaving time allocation was 7.8 hours per day. Simultaneously, the variables of age, education, experience, and family dependents significantly influenced work time allocation (F significance value < 0.05). Partially, age and experience had significant negative effects, indicating that older and more experienced weavers tend to spend less time working due to efficiency or physical limitations. In contrast, the number of family dependents had a significant positive effect, indicating greater economic pressure to work. Education was found to have no significant effect. The coefficient of determination (R²) was 64.27%, indicating a good model fit. This study contributes theoretically to the literature on labor time allocation and practically provides insights for developing policies on women's empowerment and the preservation of traditional weaving crafts in local communities.